Twelve tips for adapting grand rounds for contemporary demands. (1st February 2022) - Jattan, Aaron; Francois, Jose
Abstract: Grand rounds have evolved since inception in the early 1900s and subsequently, there has been a continual debate surrounding the best purpose for the time-honoured event. However, the purpose of grand rounds can be broadened to meet the needs of the medical community today, especially at a time where there is great distribution of medical practitioners and learners geographically and events such as COVID-19, which prevent the community from physically gathering. Using the evidence and lessons available from the literature we developed a grand rounds series with goals and objectives suited to our context. In this guide we provide twelve tips covering goal planning, logistics, presentation preparation and presentation delivery in order to illustrate how one could organize an informed grand rounds which is successful contextually.